COMPLIANCE WITH TREATMENT FOR SYSTEMIC ARTERIAL HYPERTENSION AMONG THE ELDERLY: AN INTEGRATIVE REVIEW - Marina Mendes Soares; Leonardo Oliveira Leão e Silva; Carlos Alberto Dias; Suely Maria Rodrigues; Carla Jorge Machado (Universidade Federal do Paraná, 2012)
An integrative literature review was carried out with the aim of identifying in the literature the factors which interfere with the process of complying with treatment for hypertension, especially among the elderly. Using the data-bases SciELO LILACS and Pubmed, 36 articles were selected, published between January 2006 and December 2010. From these, five major groups of factors which interfere with compliance with treatment were defined: therapeutic regime: socio-economic and demographic aspects: relationship with the healthcare service and healthcare professionals: psycho-social and cultural aspects: and family and social support. According to the literature, elderly men on a low income are the most vulnerable population, there being multiple factors which impede compliance with treatment for arterial hypertension. The most appropriate step for promoting compliance with treatment is the adoption of a multiprofessional approach in treatment for carriers of hypertension.